Subthreshold Nanosecond Laser, from Trials to Real-Life Clinical Practice: A Cohort Study - Chichan H (Dove Medical Press, 2021)
Hasan Chichan,1,2 Matthias Maus,2,* Ludwig M Heindl1,3,* 1Department of Ophthalmology, University of Cologne, Faculty of Medicine and University Hospital Cologne, Cologne, 50923, Germany; 2Sehkraft Eye Center, Cologne, 50667, Germany; 3Center for Integrated Oncology (CIO) Aachen-Bonn-Cologne-Duesseldorf, Cologne, 50937, Germany*These authors contributed equally to this workCorrespondence: Hasan Chichan Email chichan@sehkraft.deBackground: Age-related macular degeneration (AMD), a degenerative disorder, is a major cause of irreversible severe visual deterioration in the older Western population. Thus, treatments that resolve drusen may prove helpful in limiting the progression of AMD. The study aimed to evaluate the clinical outcome of sub-threshold nanosecond laser therapy (SNL) using a double-frequency nanosecond-pulsed laser with discontinuous energy beam distribution in the early stages of age-related macular degeneration (AMD).Methods: In a single-center cohort study, 64 eyes with early or intermediate AMD were treated using SNL and then compared to 77 untreated, control eyes. The primary outcome measures included the area and amount of drusen, and the secondary outcome measures included change in visual acuity and rate of drusen progression within 6 months of follow-up.Results: A total of 64 patients’ eyes following SNL treatment showed a significant reduction in the area and amount of drusen after 6 months in comparison to the corresponding values in the control group (p< 0.001, respectively). There was no significant difference in visual acuity change after 6 months in both groups (p 0.59, respectively). Within the 6-month follow-up, the rate of progression in drusen size and number was significantly lower in the SNL group (26%) than in the control group (69%; p< 0.001).Discussion: SNL therapy is a novel, promising approach for improving the macular morphology in patients with early and intermediate AMD. Further studies are necessary to reveal the potential to reduce the risk of transformation into advanced or wet AMD and to retain vision.Keywords: subthreshold nanosecond laser therapy, age-related macular degeneration, ophthalmology, drusen, ocular surgery